PERSEPSI WISATAWAN TERHADAP ATRAKSI PATROLI GAJAH TAMAN NASIONAL TESSO NILO DI KABUPATEN PELALAWAN PROVINSI RIAU - Fadri Hadi Syahputa; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The objective of this study was to find out the perception of visitors to elephant patrol attractions tesso nilo national park in pelalawan district in riau.With this study research method thati use is a qualitative method, in which researchers attempted to describe the actual condition or state by collecting data and information in the field and explain in narrative form without test hypotheses or make prediction before, while the data collection techniques in the research using observation, interviews, and documentation.Based of the result of the research that has been done in the field, the perception of visitors to elephant patrol attractions tesso nilo national park in pelalawan district in riau, basically can be said quite enjoy these attractions although there are a few things that visitors should be improved by parties associated with the elephant patrol attractions.Keywords : Perception of Visitors, Tourism Attractions, Tesso Nilo National Park, Pelalawan District.